Interactions between microbial organisms and polycyclic aromatic hydrocarbons, as investigated through the use of phospholipid fatty acid analysis - Maunder, Craig G. (My University, 2010)
PAH contamination is a significant threat to human and ecosystem health worldwide. The development of novel, efficient bioremediation systems can serve to reduce this threat by more effectively removing PAHs from contaminated environments. An improved understanding of the interactions between microbes and P AHs is essential to developing better methods to monitor P AH biodegradation, which should in turn lead to improvements in actual PAH biodegradation. This thesis developed novel process level and community-level understanding of the responses of microbes to PAH contamination, knowledge which could prove useful in the development of improved techniques for monitoring and enhancing PAH biodegradation.
The first paper (Chapter 2) examined the response of microbial communities to P AH contamination, through PLF A analysis of specific microbial communities in Hamilton Harbour, Ontario, Canada. Increased PAH contamination was found to have caused reductions in microbial biomass, and while community composition was different between sites exposed to high and low levels of PAH contamination, none of the differences in community composition could be definitively identified as having been caused by the presence of PAH. The PAH profile at the less contaminated study site was found to have changed relative to a previous study, suggesting either a change in PAH source occurred, or resuspended PAH-contaminated sediment from elsewhere in the harbour was deposited at that site.
In the second paper (Chapter 3), a novel approach using stab le carbon and radiocarbon PLF A analyses was used to establish bacterial preference for P AH as a carbon source and identify microbial carbon cycling pathways in P. frederiksbergensis bacteria. Stable and radiocarbon isotopic analyses of P. frederiksbergensis PLF A suggested P. frederiksbergensis metabolism was heterotrophic, but it was found to primarily utilize dissolved inorganic carbon (DIC) as a carbon source for PLF A biosynthesis. Isotopic data suggested metabolism of organic carbon was minimal, and as such, P. frederiksbergensis is most likely an unsuitable candidate organism for use in in situ PAH biodegradation projects.
Increased knowledge of microbial carbon cycling pathways and microbial community responses to PAH contamination will lead to improvements in P AH remediation, in turnleading to improvements in ecosystem health and reduced exposure risks to humans.
Keywords: Earth Sciences; Geography; Earth Sciences